Fighting zoonotic, rabies and public health in Colonial India - Sk Maidul Rahaman (International Journal of Public Health Science (IJPHS), 2019)
Rabies is the oldest Zoonotic diseases in the world and one of the most important Zoonotic diseases in India. It was one of the most difficult problems confronted both by the medical and veterinary authorities in colonial India. The disease is transmitted from animal to animal and from animal to man through saliva. More than 90 per cent of cases of human rabies are transmitted by dogs which was a major concern of public health. A few British officials and soldiers were bitten by dogs during the colonial period. As a result, they suffered from rabies. As ownerless dogs were infested all through the country, the disease prevailed largely at that time. Gradually, rabies became a problem to the colonial Government. Louis Pasteur obtained his first success against rabies through vaccination in 1885. At that time, Dr. Lingard, Bacteriologist, had proposed to introduce a system of anti-rabies vaccination in the Bacteriological laboratory at Poona. A similar proposal was also submitted by J.H.B. Hallen, a civil Surgeon in 1890. Later, five institutes were established in India for anti-rabies treatment. Gradually rabies patients were treated at pasture institute. Thus, this paper examines impact of rabies, treatment and veterinary public health policy in colonial India. The great Zoonotic waves of rabies that suffered public health in colonial India are also focus of this paper.